Population pharmacokinetic and pharmacodynamic model guided weight-tiered dose of AST-001 in pediatric patients with autism spectrum disorder - Lee, Soyoung; Hwang, Su-Kyeong; Cho, Jung-Sook; Ryu, Hyung Chul; Chung, Jae-Yong (Frontiers in Pharmacology, 2024)
AST-001, a novel syrup formulation of L-serine, was developed for the treatment of autism spectrum disorders (ASD) in pediatric patients. This study aimed to establish a pharmacokinetic (PK)-pharmacodynamic (PD) model to elucidate the effect of AST-001 on adaptive behavior in children with ASD. Due to the absence of PK samples in pediatric patients, a previously published population PK model was used to link the PD model by applying an allometric scale to body weight. The time courses of Korean-Vineland Adaptive Behavior Scale-II Adaptive Behavior Composite (K-VABS-II-ABC) scores were best described by an effect compartment model with linear drug effects (Deff, 0.0022 L/μg) and linear progression, where an equilibration half-life to the effect compartment was approximately 15 weeks. Our findings indicated a positive correlation between the baseline K-VABS-II-ABC score (E0, 48.51) and the rate of natural progression (Kprog, 0.015 day−1), suggesting enhanced natural behavioral improvements in patients with better baseline adaptive behavior. Moreover, age was identified as a significant covariate for E0 and was incorporated into the model using a power function. Based on our model, the recommended dosing regimens for phase III trials are 2, 4, 6, 10, and 14 g, administered twice daily for weight ranges of 10–13, 14–20, 21–34, 35–49, and >50 kg, respectively. These doses are expected to significantly improve ASD symptoms. This study not only proposes an optimized dosing strategy for AST-001 but also provides valuable insights into the PK-PD relationship in pediatric ASD treatment.